Internationalization of SMEs: a literature review. - EL MOUDDEN Maryam; BALHADJ Said (African Scientific Journal, 2024)
Abstract Opening up to the international market will encourage small and medium-sized businesses to develop and grow. To achieve this, small and medium-sized enterprises need to prepare themselves to compete, survive and even grow on the international market. The aim of this article is to carry out a literature review with the aim of clarifying the concept of SME internationalization, and this is thanks to the recognition that occupies the role of the SME in the economic development of the country. In this work, we will review the literature in detail on the concept of SME internationalization, then look at the main theories of internationalization, and finally demonstrate the situation of Moroccan SME exporters and their importance in Morocco’s economy and foreign trade. Keywords : SME, internationalization of companies, exporting.